2018
DOI: 10.1242/dev.162107
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of Capsaspora owczarzaki, a close unicellular relative of animals

Abstract: How animals emerged from their unicellular ancestor remains a major evolutionary question. New genome data from the closest unicellular relatives of animals have provided important insights into the evolution of animal multicellularity. We know that the unicellular ancestor of animals had an unexpectedly complex genetic repertoire, including many genes that are key to animal development and multicellularity. Thus, assessing the function of these genes among unicellular relatives of animals is key to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 45 publications
(57 reference statements)
0
46
0
Order By: Relevance
“…2016 ). Transgenics systems are currently being developed for holozoan protists ( Parra-Acero et al. 2018) , and the data presented here provide important information for the expression of artificial transgenes.…”
Section: Discussionmentioning
confidence: 99%
“…2016 ). Transgenics systems are currently being developed for holozoan protists ( Parra-Acero et al. 2018) , and the data presented here provide important information for the expression of artificial transgenes.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic and transcriptomic data are available for multiple representatives characterized by diverse cell morphologies, some of which can even form multicellular structures 46 . Until recently, only transient transformations had been achieved for some opistokonts such as the filasterean Capsaspora owczarzaki 48 , the ichthyosporean Creolimax fragrantissima 49 and the choanoflagellate Salpingoeca rosetta 21 . Through the EMS initiative, we report on evidence for transient transformation of the ichthyosporean Abeoforma whisleri, isolated from the digestive tract of mussels, and review a recently published stable transformation protocol for S. rosetta achieved by using the selectable puromycin N-acetyl-transferase gene (Fig.…”
Section: Nature Methodsmentioning
confidence: 99%
“…Initial descriptions of Capsaspora showed that it has dynamic filopodia (Stibbs et al, 1979), and a recent study revealed that these filopodia contact the substrate and appear to hold the cell body above the surface (Parra-Acero et al, 2018). We examined filopodia behaviour in live cells, by performing time-lapse microscopy of adherent Capsaspora cells transfected with a membrane marker (NMM-mCherry) (Parra-Acero et al, 2018). We observed that filopodia not only hold the cell over the surface but appear to actively participate in its motility ( Figure 2D).…”
Section: Resultsmentioning
confidence: 99%